2012
DOI: 10.1016/j.jclinane.2011.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing unexpected disposition after orthopedic ambulatory surgery

Abstract: Study Objective To analyze whether patient characteristics, ambulatory facility type, anesthesia provider and technique, procedure type, and temporal factors impact the outcome of unexpected disposition after ambulatory knee and shoulder surgery. Design Retrospective analysis of a national database. Setting Freestanding and hospital-based ambulatory surgery facilities. Measurements Ambulatory knee and shoulder surgery cases from 1996 and 2006 were identified through the National Survey of Ambulatory Surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 12 publications
1
27
0
Order By: Relevance
“…21,22 Examining the impact of the type of anesthesia in a cohort limited to hip fracture patients in New York, Neuman et al . 22 discovered beneficial effects of regional versus general anesthesia in respect to mortality and pulmonary complications.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Examining the impact of the type of anesthesia in a cohort limited to hip fracture patients in New York, Neuman et al . 22 discovered beneficial effects of regional versus general anesthesia in respect to mortality and pulmonary complications.…”
Section: Discussionmentioning
confidence: 99%
“…28,[35][36][37] In this context, large database studies have recently gained widespread interest and addressed questions of comparative effectiveness of various anesthetic techniques. 26,38 Other drivers in anesthesia practice include institutional preferences and physician-or patient-related factors. 26 Surveys among practicing anesthesiologists have shown that adequate training poses a major driving factor in the application of regional anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…3 Furthermore, shoulder surgery is associated with a three-fold increase in unanticipated hospital admissions compared with other orthopedic ambulatory surgeries. 4 Specific reasons for this association are unclear. Nevertheless, since shoulder surgery is one of the most painful common surgeries, 3,5 anesthesiology care may be particularly important in influencing patient-centred and health system outcomes.…”
Section: Résumémentioning
confidence: 99%